Reinterpreting King Solomon's Problem: Malice and Mechanism Design - GUHA, Brishti (Institutional Knowledge at Singapore Management University, 2014)
I argue for an alternative interpretation of King Solomon's problem in terms of one of the two claimants being “malicious”. A “malicious” claimant places no intrinsic value on the object but derives utility from depriving the rival claimant. This new interpretation permits a simpler solution than those considered in the literature; I derive a mechanism that induces truthful revelation where the equilibrium involves a single round of elimination of weakly dominated strategies, and no monetary transfers. I consider extensions which allow for the malicious claimant to also place some low but positive intrinsic valuation on the object; I also discuss the possibility of two-sided malice, and provide examples of several real-life contexts to which the mechanism or its extensions are applicable.